Designing Promotional Media for “Dolas Songket Silungkang” in Sawahlunto City - Arya Primanda; Harissman (Indonesian Journal Publisher, 2025)
Despite the uniqueness of its handmade process, use of natural dyes, and rich Minangkabau cultural symbolism, this enterprise faces challenges in market visibility due to ineffective promotional strategies. This design based research aims to develop an integrated visual communication strategy to enhance brand awareness, customer engagement, and market expansion for Dolas Songket Silungkang. Employing qualitative methods observation, interviews, questionnaires, and SWOT analysis the project identifies key obstacles in current promotional media. The creative solution involves producing an audiovisual advertisement enriched with motion graphics and storytelling, supported by print and digital media such as catalogs, posters, social media content, and merchandise. The visual concept combines traditional and modern aesthetics through the use of elegant typography, cultural color palettes, and fashion-forward product displays. This approach not only promotes the brand but also contributes to preserving the cultural heritage of Minangkabau textile art. The project demonstrates how design interventions can improve promotional effectiveness and reinforce local identity in contemporary markets